The glycosylphosphatidylinositol-anchored protein repertoire of Babesia bovis and its significance for erythrocyte invasion - Rodriguez, Anabel Elisa; Florin-Christensen, Mónica; Flores, Daniela; Echaide, Ignacio Eduardo; Suarez, Carlos Esteban; Schnittger, Leonhard (2017)
Glycosylphosphatidylinositol-anchored proteins are abundant on the surface of pathogenic protozoans and might play an important role for parasite survival. In the present work, the relevance of GPI-anchored proteins for erythrocyte invasion of the cattle hemoparasite Babesia bovis was studied. We show that cleavage of GPI-anchored antigens from the merozoite parasite stage by phosphatidylinositol-specific phospholipase C abolished invasion of erythrocytes demonstrating the importance of this class of molecules for parasite propagation. In addition, the repertoire of GPI-anchored proteins of B. bovis was predicted with high fidelity by searching its genome with available web-based bioinformatic tools. Altogether 17 GPI-anchored proteins were identified, 5 of which represent the already characterized variable merozoite surface antigens (VMSAs). Fifteen of the identified GPI-anchored proteins contain 2–26 amino acid repeats indicating that they are likely involved in functions of recognition, adhesion, or transport. Repeats were found to contain an increased frequency of proline, indicative of unstructured regions; and were estimated to be 3.21 times more hydrophilic than non-repeat regions. This suggests that they might represent eminent antibody epitopes. The majority of the putative GPI-anchored antigens reported in this work have so far remained unnoticed, though they may represent potential candidates for inclusion in a subunit vaccine.